2004
DOI: 10.1152/ajpheart.01006.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rho/Rho kinase signaling pathway by reactive oxygen species in rat aorta

Abstract: . Activation of Rho/Rho kinase signaling pathway by reactive oxygen species in rat aorta. Am J Physiol Heart Circ Physiol 287: H1495-H1500; 2004; 10.1152/ajpheart.01006.2003.-Evidence indicates that both the Rho/ Rho kinase signaling pathway and reactive oxygen species (ROS) such as superoxide and H 2O2 are involved in the pathogenesis of hypertension. This study aimed to determine whether ROS-induced vascular contraction is mediated through activation of Rho/Rho kinase. Rat aortic rings (endothelium denuded)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
185
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(196 citation statements)
references
References 45 publications
9
185
1
Order By: Relevance
“…Nimnual et al (26) demonstrated a down-regulation of Rho by Rac-induced ROS in HeLa cells. However, another study reported an increase in Rho activation by ROS in rat aortic rings (27). A recent article reported that H 2 O 2 is able to regulate both phosphatase and protein kinase activities (29), which could readily affect downstream RhoGTPase signaling.…”
Section: Discussionmentioning
confidence: 98%
“…Nimnual et al (26) demonstrated a down-regulation of Rho by Rac-induced ROS in HeLa cells. However, another study reported an increase in Rho activation by ROS in rat aortic rings (27). A recent article reported that H 2 O 2 is able to regulate both phosphatase and protein kinase activities (29), which could readily affect downstream RhoGTPase signaling.…”
Section: Discussionmentioning
confidence: 98%
“…101 In addition, RhoA/ Rho-kinase suppresses eNOS gene expression and enzyme activity in the penis 13 and erectile 105 suggesting an additional means of interaction between eNOS-mediated relaxant and RhoA/Rho-kinase-mediated contractile pathways in the penis. Moreover, as shown in nonpenile vascular beds, ROS activate the RhoA/Rho-kinase pathway by promoting increased migration of RhoA to the plasma membrane and its activation, 106 thus stimulating vasoconstriction. Furthermore, Rhokinase stimulates NAD(P)H oxidase with consequent increase in the production of ROS, 107 further contributing to endothelial dysfunction.…”
Section: Rhoa/rho-kinase Contractile Pathwaymentioning
confidence: 95%
“…[106][107][108] Endothelial function and hypertension in aging Y Higashi et al Several investigators have shown an interaction between the RhoA/ ROCk pathway and ROS. 109,110 Indeed, ROS induced by hyperglycemia enhances ROCK activity, leading to atherothrombogenesis through an increase in expression of plasminogen activator inhibitor-1 in vascular endothelial cells. 111 It is well known that cigarette smoking decreases NO bioavailability through the production of ROS.…”
Section: Tetrahydrobiopterin (Bh 4 )mentioning
confidence: 99%